Numerical simulation of flow around a simplified high-speed train model using OpenFOAM - Ishak, I. A.; Ali, M S M; Shaikh Salim, S A Z (IOP Publishing, 2018)
Detailed understanding of flow physics on the flow over a high-speed train (HST) can be accomplished using the vast information obtained from numerical simulation. Accuracy of any simulation in solving and analyzing problems related to fluid flow is important since it measures the reliability of the results. This paper describes a numerical simulation setup for the flow around a simplified model of HST that utilized open source software, OpenFOAM. The simulation results including pressure coefficient, drag coefficient and flow visualization are presented and they agreed well with previously published data. This shows that OpenFOAM software is capable of simulating fluid flows around a simplified HST model. Additionally, the wall functions are implemented in order to minimize the overall number of grid especially near the wall region. This resulted in considerably smaller numbers of mesh resolution used in the current study compared to previous work, which leads to achievement of much reasonable time simulation and consequently reduces the total computational effort without affecting the final outcome.